A Comparison of Different Doses of Sufentanil Combined With Flurbiprofen Axetil In Postoperative Analgesia for Children Undergoing Innominate Osteotomy in China - Chowdhury, Alvira Jafar; Barua, Subrata; Das, Pritam; Wei, Wang Rui; Yuan, Zhang Meng (Journal of Chittagong Medical College Teachers’ Association, 2017)
To evaluate the analgesic efficacy of different doses of sufentanil combined with flurbiprofen axetil in children undergoing innominate osteotomy. Ninety children scheduled for elective innominate osteotomy under general anesthesia were enrolled and randomly divided into 3 groups. All the children received 1mg/kg flurbiprofen axetil intravenously before skin incision for pre-emptive analgesia. Patient Controlled Intravenous Analgesia (PCIA) was started at the end of the operation with the following composition: Sufentanil 1.5 g/kg and ondansetron 0.1 mg/kg in 0.9% NS 100ml (Group N1) sufentanil 2.0 g/kg and ondansetron 0.1 mg/kg in 0.9% NS 100ml (Group N2) and sufentanil 2.5 g/kg and ondansetron 0.1 mg/kg in 0.9% NS 100ml (Group N3). FLACC scores and Ramsay sedation scores were recorded at 2, 4 ,8 ,12 ,24 and 36h after the operation;the PCA button press number and side effects were observed and recorded. FLACC scores in group N1 were higher than group N2 and N3 (p<0.05).Ramsay scores in group N1 were lower than group N2 and N3 (p<0.05).There were no significant differences in FLACC scores and Ramsay scores between group N1 and N2 (p> 0.05).The incidence of side effects was significantly higher in group N3 compared with group N1 and N2 (p<0.05). Combined with 1mg/kg flurbiprofen axetil for preemptive analgesia , PCIA with sufentanil 2.0 g/kg and ondansetron 0.1 mg/kg in 0.9% NS 100ml may be an effective postoperative analgesia solution for children undergoing innominate osteotomy ,with less side effects. JCMCTA 2016 ; 27 (2) : 77 - 80